Short report: Molecular identification of Trichinella papuae from a Thai patient with imported trichinellosis - Intapan P.M. (2014)
Previously, we reported the presence of imported trichinellosis in a Thai worker returning from Malaysia, who presented with progressive generalized muscle hypertrophy and weakness after eating wild boar meat. This work analyzed a partial small subunit of a mitochondrial ribosomal RNA gene of Trichinella larvae isolated from the patient. The results showed complete identity with a mitochondrial RNA gene of Trichinella papuae (GenBank accession no. EF517130). This is the first report of imported trichinellosis in Thailand caused by T. papuae. It is possible that T. papuae is widely distributed in the wildlife of Southeast Asia. Copyright © 2011 by The American Society of Tropical Medicine and Hygiene.